Capital Controls and the Cost of Debt - Andreasen, Eugenia (IMF Working Papers; Working Paper ;, 2017)
Using a panel data set for international corporate bonds and capital account restrictions in advanced and emerging economies, we show that restrictions on capital inflows produce a substantial and economically meaningful increase in corporate bond spreads. A number of heterogeneities suggest that the effect of capital controls on inflows is particularly strong for more financially constrained firms, establishing a novel channel through which capital controls affect economic outcomes. By contrast, we do not find a robust significant effect of restrictions on outflows.